2010
DOI: 10.1118/1.3483780
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of instantaneous source speed for a HDR brachytherapy unit using an optical fiber based detectora)

Abstract: To the best of the authors' knowledge, the authors directly measured for the first time the instantaneous speed profile of a radiation source in a HDR brachytherapy unit traveling from the unit safe to the end of the catheter and between interdwell distances. The method is feasible and accurate to implement on quality assurance tests and provides a unique database for efficient computational simulations of the transient dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…Although there is good agreement with previous results, the use of a single detector is not recommended for an accurate evaluation of the source speed as only average source speed is measured. Using the MP array, with its constant detector spacing and a sampling rate of 100 µs, instantaneous speed measurements could be performed for any positions within treatment related volume, similar to the method proposed by Minamisawa et al 13 , which uses an optical fibre system and digital oscilloscope with timing resolution of 1 nanosecond.…”
Section: Ivc Evaluation Of Hdr Source Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is good agreement with previous results, the use of a single detector is not recommended for an accurate evaluation of the source speed as only average source speed is measured. Using the MP array, with its constant detector spacing and a sampling rate of 100 µs, instantaneous speed measurements could be performed for any positions within treatment related volume, similar to the method proposed by Minamisawa et al 13 , which uses an optical fibre system and digital oscilloscope with timing resolution of 1 nanosecond.…”
Section: Ivc Evaluation Of Hdr Source Trackingmentioning
confidence: 99%
“…The transit dose of a HDR unit was quantified by Fonseca et al 12 , based upon calculations of the instantaneous source speed and a Monte Carlo (MCNP5) simulated transit dose profile. The instantaneous source speed, measured using a high resolution optical fiber based detector system 13 was used to give weighting to the simulated transit dose and allow for an accurate calculation of transit dose values. The results were verified experimentally using radiochromic film and showed that the transit component can be significant, reaching up to a few hundred cGy per application.…”
Section: Introductionmentioning
confidence: 99%
“…The transit dose component of a brachytherapy source movement from the safe to the dwell positions, between the dwell positions, and when returning to the safe has been studied previously, [1][2][3][4][5][6][7] reporting differences up to a factor of 10 for the source speed for the same afterloader. 8 The effect of these differences on the transit dose component for clinical brachytherapy treatments performed with a HDR 192 Ir source was evaluated recently.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported measurements were performed using a video camera, 1,4 up to 30 frames per second (fps), an ionization chamber, 3 oscilloscopes connected to the afterloader, 9 optical fibers to detect induced Cerenkov radiation, 5 and film dosimetry. 2 This work describes the speed profiles obtained using a high speed video camera.…”
Section: Introductionmentioning
confidence: 99%
“…This contribution may become significant (>5%) if it is not corrected for appropriately [25]. Transit dose correction based on average source speed fails to accurately correct the dose, indicating that accurate measurement of the source acceleration and speed profile should be considered [58]. Source kinematics differ between afterloading systems [59].…”
Section: Testmentioning
confidence: 99%